An Insight Into the Intestinal Web of Mucosal Immunity, Microbiota, and Diet in Inflammation - Yap, Yu Anne; Mariño, Eliana (Frontiers in Immunology, 2018)
​The rising global incidence of autoimmune and inflammatory conditions can be attributed to changes in the large portion of the immune system that belongs to our gastrointestinal tract (GI). The intestinal immune system serves as gatekeepers to prevent pathogenic invasions through the gut mucosa and maintain homeostasis. Inappropriate immune responses against food and microbial antigens can cause inflammatory disorders such as inflammatory bowel disease (IBD) and celiac disease. Diet influences our gut microbiota causing a shift in the balance of the microbial communities, which also play an essential role in maintaining gut homeostasis. Under beneficial dietary habits, the gut microbiota produces metabolites, which are important in maintaining metabolic and immune homeostasis. Thanks to the advances in integrative omics over the last decades, the gut microbiota has been increasingly studied as a fundamental contributor to the state of health and disease. A large body of evidence in recent years by ourselves and others have uncovered the link between the gut microbiota, diet and the immune system and specific diseases such as autoimmune type 1 diabetes (T1D), obesity and type 2 diabetes (T2D), cardiovascular disease, infections, allergies, asthma, and IBD. Thus, the power of these three dynamic components; mucosal immunity, diet, and the gut microbiota, can be harnessed in tandem for the prevention and treatment of inflammatory diseases.